Parametric Modeling and Multi-body Dynamics Simulation of RV Reducer - Qi Lu; Weidong He (Jixie chuandong)
The CAD parametric modeling of RV reducer parts is carried out， and the parametric assembling model of cycloidal gear modification amount and dimension error of parts is established. Based on multi-body dynamics simulation technology， with bearing clearance， dynamics simulation model that includes gear contact and pin-slot contact is established. Considering the small period factors that affect the angular transmission error of RV reducer， the diameter of the needle tooth center circle and the diameter of the needle tooth groove in the same assembly dimension chain are selected to combine the errors， and the dynamics simulation is carried out under rated working conditions，the variation rule of the angular transmission error is analyzed.